2019
DOI: 10.1002/rra.3550
|View full text |Cite
|
Sign up to set email alerts
|

The effects of extremes and temporal scale on multifractal properties of river flow time series

Abstract: For accurate forecasting of extreme events in rivers, streamflow time series with sub-daily temporal resolution (1-6 hour) are preferable, but discharge time series for long rivers are usually available at daily or monthly resolution. In this study, the scaling properties of hourly and daily streamflow time series were measured. As an innovation, the effects of extreme values on the multifractal behavior of these series were evaluated. Interestingly, both hourly and daily discharge records led to nearly identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Of all the methods mentioned, the DFA method has been proven to have exceptional accuracy [10,11] in analyzing fractal properties not only for geomagnetic data [3,5,6,[12][13][14] but for other purposes as well, as noted by Kantelhardt et al [15]. On the other hand, the newer method of r-DFA has been prominently utilized in analyzing hydrological data [16][17][18] and to a lesser extent, other types of data such as meteorological data [19], medical data [20], and solar activity data [21]. As for geomagnetic data, to date, it has been subjected to the method of r-DFA [22], but not to an extensive degree.…”
Section: Introductionmentioning
confidence: 99%
“…Of all the methods mentioned, the DFA method has been proven to have exceptional accuracy [10,11] in analyzing fractal properties not only for geomagnetic data [3,5,6,[12][13][14] but for other purposes as well, as noted by Kantelhardt et al [15]. On the other hand, the newer method of r-DFA has been prominently utilized in analyzing hydrological data [16][17][18] and to a lesser extent, other types of data such as meteorological data [19], medical data [20], and solar activity data [21]. As for geomagnetic data, to date, it has been subjected to the method of r-DFA [22], but not to an extensive degree.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, empirical studies have demonstrated the effectiveness of fractal geometry in describing natural phenomena such as mountains, clouds, tree trunks, river networks, and coastlines. Fractal geometry's ability to capture the self-similarity and irregularity of natural structures can provide a more accurate and detailed understanding of these phenomena (Hekmatzadeh et al, 2018;Mandelbrot, 1982). It is possible to assign a fractal dimension to every part of nature by using fractal theory and the idea that many phenomena within nature are in order despite chaos (Mofidi et al, 2021;Mohammadi Khoshoui, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Eng et al, 2013;Fazel et al, 2017;Nilsson et al, 2005;Radinger et al, 2018;Torabi Haghighi and Kløve, 2017). Anthropogenic interference, such as land use and cover change and river modification as well as climate change, can influence major characteristics of flow regimes (Ashraf et al, 2018;Hekmatzadeh et al, 2020;Mustonen et al, 2016;Pirnia et al, 2019;Torabi Haghighi et al, 2019;Yaraghi et al, 2019). Managing large rivers is especially challenging as they are transboundary, with different upstream and downstream water management interests.…”
Section: Introductionmentioning
confidence: 99%